1958
DOI: 10.1111/j.1365-2621.1958.tb17575.x
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic Autolysis of Muscle: Biochemical and Microscopic Modifications Occurring in Rabbit and Lamb Muscle During Aseptic and Anaerobic Storage

Abstract: 111 vivo muscle is normally sterile. This tissue becomes highly contaminated post morteni by aerobic and anaerobic flora, however, if it is stored at normal or higher temperature and if it is not protected against contamination from these sources by rather drastic technics. I t has been shown that irradiation can protect muscle from such contamination, but we know that sterilization doses of radiation do not completely inhibit proteolysis (8). We have chosen not to rely on such sterilizations for our first exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1961
1961
1977
1977

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…14, July Flamed samples from adrenaline treated rabbits K I5 ( I ) 6.82, (2) 6.64 Food Agric., 1963, Vol.…”
Section: Trichloroacetic Acid-soluble N (Non-protein N )mentioning
confidence: 99%
“…14, July Flamed samples from adrenaline treated rabbits K I5 ( I ) 6.82, (2) 6.64 Food Agric., 1963, Vol.…”
Section: Trichloroacetic Acid-soluble N (Non-protein N )mentioning
confidence: 99%
“…At ageing temperatures, slow naturally occurring enzyme activity occurs in meat and this decreases with ageing time. 5 Proteases produce an increase in free amino acids, principally alanine, glutamic acid, leucine and cystine-liberated from the sarcoplasniic proteins. The importance of amino acids as beef aroma precursors is well established, both per se6 and in conjunction with other compounds, e.g., in Strecker degradations and Maillard reacti0ns.l-3 Lipolytic enzymes also operate and during ageing there is an increase in free fatty acid concentration.7~ 8 Fatty acids, particularly the cl8 unsaturated acids are precursors of carbonyl comp0unds.9-~~ Such compounds have been implicated in meat flavour, particularly fat flavourlz and roasted flavour13 and total carbonyl concentration increases in beef muscle during ageing.l* Other reactions relevant to flavour production which occur during conditioning include the breakdown of adenosine triphosphate forming inosine, hypoxanthine and ribose, which when heated in the presence of various amino acids give rise to meaty o d o~r s .~, 15, l 6 The Strecker degradation of amino acids is catalysed by inosinic acid.17 However, Rhodes has found no correlation between nucleotide degradation and flavour changel8 while Lyaskovskaya and Safronova also concluded that hypoxanthine does not participate in the development of meat aroma.19 An increase in concentration of the soluble carbohydrate intermediates of glycolysis also occurs on ageing and some glycogen is converted into glucose by a-amylase.l5 This, together with the simultaneous production of free amino acids, provides a pool of Maillard reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques available at the present time for obtaining axenic meat are based either on a superficial decontamination by means of alcohol (Sharpe, 1963) or antibiotics (Van den Berg, 1964) aseptic sampling in a special surgical room (Zender et al, 1958) in a laminar air flow (Buckley et al, 1976) or by application of a surgical isolator procedure (Ockerman et al., 1964;Brassine and Dubois, 1975). The major disadvantages of these techniques are insufficient decontamination with alcohol (Sharpe, 1963), impossibility in obtaining growth of inoculated bacterial strains after utilization of antibiotics ( Van den Berg, 1964) or the high costs involved in techniques using surgical isQlators (Ockerman et al, 1964;Brassine and Dubois, 1975).…”
Section: Discussionmentioning
confidence: 98%